Impact of Transformational and Transactional Attributes of School Principal Leadership on Teachers’ Motivation for Work - Hyseni Duraku, Zamira; Hoxha, Linda (Frontiers in Education, 2021)
The current study aims to identify the impact of transformational and transactional attributes of school principal leadership on teachers’ motivation for work. A sample of 357 Kosovar public middle school teachers was assessed using the Work Tasks Motivation Scale for Teachers (WTMST) and the Multifactor Leadership Questionnaire (MLQ). Results revealed that transformational leadership attributes, idealised influence, and inspirational motivation predict autonomous motivation in teachers; individual consideration predicts motivation for complementary tasks; and contingent reward significantly predicts motivation for student evaluations. The present study findings can serve as a support in improving the quality of education in low- and middle-income countries.